The role of Egyptian workers in the 2011 uprising: a view from below - Gjergji, Iside (2013)
An oft-used representation of the Egyptian mass uprising in Western journalistic and academic debates is: through the use of social networks, young people have been able to quickly mobilize millions of protesters. Egyptian uprising is often interpreted as social and political phenomena, mostly instigated by middle-classes, highly educated and unemployed young people. In this perspective, workers’ movement and its decadal struggles receive less attention and is considered a priori irrelevant. This paper aims to contribute some essential steps in considering the recent Egyptian uprising as a complex historical process, in which labour movement’s role was pivotal. At methodological level, the paper seeks to combine literature, quantitative and qualitative research methods.